Synthesis of polycyclic indole skeletons by a gold(I)-catalyzed cascade reaction - Wang, Tao; Shi, Shuai; Pflästerer, Daniel; Rettenmeier, Eva; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2014)
The conversion of simple, easily available urea-substituted 3-phenylpropargyl alcohols catalyzed by a simple IPr-gold(I) catalyst in a gold(I)-catalyzed cascade reaction composing of a gold-catalyzed nucleophilic addition and a subsequent gold-catalyzed substitution reaction delivers 1H-imidazo[1, 5−a]indol-3(2 H)-ones. Other gold(I) catalysts or silver catalysts gave lower yields and often gave other side products. Gold(III) and copper(II) catalysts decomposed the starting material. Twelve examples, including donor and acceptor substituents on the distal nitrogen of the urea substructure, are provided. An X-ray crystal structure analysis confirmed the structural assignment. The mechanistic investigation including isolation and further conversion of intermediates and reactions with enantiopure starting materials indicated that after the nucleophilic-addition step, the substrate undergoes an SN1-type benzylic substitution reaction at the indolyl alcohol intermediate or an intramolecular hydroamination reaction of the 2-vinylindole intermediate.
First published: 20 December 2013
Gesehen am 15.10.2020